Cationic Noble-Gas Hydrides: From Ion Sources to Outer Space - Grandinetti, Felice (Frontiers in Chemistry, 2020)
Cationic species with noble gas (Ng)-hydrogen bonds play a major role in the gas-phase ion chemistry of the group 18 elements. These species first emerged more than ninety years ago, when the simplest HeH+ and HeH2(+) were detected from ionized He/H2 mixtures. Over the years, the family has considerably expanded, and currently includes various bonding motifs that are investigated with intense experimental and theoretical interest. Quite recently, the results of these studies have acquired new and fascinating implications. The diatomic ArH+ and HeH+ were, in fact, detected in various galactic and extragalactic regions, and this stimulates intriguing questions concerning the actual role in the outer space of the Ng-H cations observed in the laboratory. The aim of this review is to briefly summarize the most relevant information currently available on the structure, stability, and routes of formation of these fascinating systems.